Spatial and Social Discontinuities in Burial Practice and the Privatisation of Mortuary Space in Bronze Age Cyprus. (23rd January 2019) - Webb, Jennifer
Abstract : This paper looks at spatial and social discontinuities in burial practice and in the intensity with which burial places became contested spaces in Bronze Age Cyprus. Early and Middle Bronze Age cemeteries are typically viewed as communal landscapes associated with ancestral claims to place and community, a process that involved varied levels of social negotiation and posturing linked at some sites with ritual and material culture elaboration and the likely use of some tombs as mortuary shrines. In the Late Bronze Age there was a shift, in some settlements, to intramural burial. This 'privatisation' of mortuary space has been linked with the rise of more rigid political and economic structures and the development of an 'urban mindset'. The public/private dichotomy across the Middle to Late Bronze Age transition, however, appears to have been overstated. While earlier, relatively fluid associations did give way to more structured relationships, likely reducing the need for community-wide strategies of affiliation, this did not happen evenly across the island and at many settlements it did not happen at all. The boundary between intraand extramural burial, furthermore, was never absolute and the inclusive egalitarian village cemetery may never have been a reality, with the dead perhaps always viewed as belonging to lineage groups rather than to a wider ancestral community. Variations in the place value of burial are visible throughout the Bronze Age and the apparent shift to intramural burial is likely to have been determined by historically contingent circumstances rather than changes in ideology or emerging notions of privacy or hierarchy.